Neuroleptic malignant syndrome: a case report - Muhammad Kashif; Asad Tamizuddin Nizami; Kareem Mirza, Kainat (Journal of the Pakistan Medical Association, 2025)
Neuroleptic malignant syndrome is a serious adverse drug reaction associated with antipsychotic medications. The cause is dopamine blockade caused by these drugs. We are presenting the case report of a 25-year old male patient, who presented to our psychiatry emergency facility, with post-ictal behavioural disturbances. He required rapid tranquilization and subsequently developed symptoms of NMS due to the first-generation antipsychotics. His creatinine phosphokinase levels were markedly elevated, reaching 89900 and 105000 at different points. Early diagnosis and prompt management played an important role in his recovery. This case emphasizes the importance of early diagnosis and treatment to reduce mortality and morbidity associated with NMS. The withdrawal of antipsychotics is the mainstay of management, along with supportive treatment. Keywords: Neuroleptic Malignant syndrome (NMS), Creatinine Phosphokinase level (CPK), 4 times a day (QID).